2011
DOI: 10.1016/j.chroma.2011.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of first dimension phase selectivity in online comprehensive two dimensional liquid chromatography (LC×LC)

Abstract: In this study, we examined the effect of first dimension column selectivity in reversed phase (RP) online comprehensive two dimensional liquid chromatography (LC × LC). The second dimension was always a carbon clad metal oxide reversed phase material. The hydrophobic subtraction model (HSM) and the related phase selective triangles were used to guide the selection of six different RP first dimension columns. Various kinds of samples were investigated and thus two different elution conditions were needed to cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The chromatograms corresponding to online LC×LC runs, where gradient elution was used in both 1 D and 2 D, are explained in detail in our previous work 9 . A general description of the conditions is provided here:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatograms corresponding to online LC×LC runs, where gradient elution was used in both 1 D and 2 D, are explained in detail in our previous work 9 . A general description of the conditions is provided here:…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure for sample preparation and system configuration is described in detail in the given reference 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Their approach shows that, due to their high retentivity and hydrophobicity, carbon‐clad columns provide rather different selectivities than the vast majority of alkyl bonded RP columns. The conclusion of Zhang et al that these columns should be used as the 2 D column in RPLC × RPLC systems has recently been adopted by Gu et al []. Jandera and coworkers used linear‐free‐energy relationships (LFER) [] as a tool for comparing the selectivity of several LC columns [].…”
Section: Quality Descriptors In Lc × Lc Optimization: the Role Of Peamentioning
confidence: 99%
“…Mentioned combinations of different separations provide high separation orthogonality and yield increased number of identified proteins . The combination of HILIC‐RPLC has shown that equal or even higher orthogonality can be achieved compared to the most commonly employed SCX‐RPLC systems and the peptide separation combination of high pH RP and RP at low pH .…”
Section: Introductionmentioning
confidence: 99%